KRAS and NRAS mutations in Nordic population-based and real-world metastatic colorectal cancer cohorts - Österlund, Emerik; Ristimäki, Ari; Nunes, Luís; Kytölä, Soili; Aho, Sonja; Heervä, Eetu; Uutela, Aki; Lehtomäki, Kaisa; Stedt, Hanna; Halonen, Päivi; Kontiainen, Joel; Muhonen, Timo; et al. (Nature Publishing Group, 2026)
Background
KRAS and NRAS mutations (mt) are drivers in metastatic colorectal cancer (mCRC). We studied frequencies, characteristics, treatments, and outcomes of different KRASmt and NRASmt in population-based and real-world settings.
Methods
Three Nordic cohorts were combined and molecularly characterised for KRAS, NRAS, and BRAF-V600E hotspot mutations.
Results
Of 2649 mCRC patients, 2118 were molecularly classified. KRASmt were seen in 49%, NRASmt in 4%, RAS&BRAFwt in 33%, and BRAF-V600Emt in 14%. No differences in clinical characteristics were observed between KRASmt and NRASmt. Median overall survival (OS) was longest among RAS&BRAFwt, intermediate among KRASmt and NRASmt, and shortest among BRAF-V600Emt (28.3 vs 21.4 vs 26.3 vs 9.2 months, respectively). Among the eight most common KRASmt, the only clinical difference was that KRAS-G12S had more distant lymph node metastases (38% vs 18–27%, p = 0.041). KRAS-G12S had shorter OS than KRAS-G12V, KRAS-G12C, KRAS-G12A, and KRAS-G13D. The differences were smaller in treatment groups but withstood in multivariable models. The three most common NRASmt did not differ clinically.
Conclusion
KRASmt and NRASmt are seen in 49% and 4% of mCRC, respectively. No clinically relevant differences were observed between different RASmt. KRASmt is a common subgroup for which the outcome hopefully can be improved with newly developed drugs.